“Evaluación Financiera al Supermercado Lizbeth de la Ciudad de Loja, período 2014 - 2015 - Arévalo Quizhpe, Diana Elizabeth (2017)
This thesis entitled: "FINANCIAL EVALUATION TO THE LIZBETH SUPERMARKET OF THE CITY OF SHOP, PERIOD 2014-2015", is executed within the parameters established by the Regulation of the Academic Regime of the National University of Loja, as a prerequisite to Opt for the degree and title of Engineer in Accounting and Auditing. To meet the objectives: "Determined the economic and financial structure to know the different items that intervene in the economic position of the business." It began with the collection of the information, from which the vertical and horizontal analysis of the financial statements of the years 2014-2015 was carried out, obtaining as a result that the current assets there is an increase of $ 161,032.35 equivalent to 20.28% ; With respect to liabilities, an increase of $ 169,816.47, representing 29.35%, resulted in a decrease of $ -8,784.12 representing -4.08%. Referring to the debt ratio in 2014 has 72.90% and in the year 2015, 78.40% indicates that the company has a high level of indebtedness with financial institutions, due to the purchase of fixed assets, Within the activity index is the average collection period that shows a result of 0.89 times in the year 2014 and 2015 of 0.51 times, without ignoring that in the year 2015 the collection behavior has improved considerably, as well the index Of profitability in 2014 yields 0.10%, of the sales with a favorable 6 variation for the year 2015, that indicates a 3.30%, that is to say that for every dollar sold you get 0.033 cents of profit. After analyzing and revising the financial statements, the indicators that determine the liquidity, indebtedness, activity and profitability are applied, Dupont System, Eva, which allowed to know the level of operations of the company. The financial evaluation was done using evaluation methods such as the Dupont System, resulting in 2.41% in 2014 and 2015 of 2.29% which is not favorable to the Supermarket because the maximum percentage that a company must have for To continue operating is 10%, ie it does not have an efficient use of its fixed assets on the rotation of the same, EVA gives a negative aggregate economic result in the year 2014 of $ -32,356.48 and for the year 2015 of $ - 109,969,04, ie the company does not advance to cover the cost of capital, evidencing a decrease that destroys the value of the capital resources used. Finally, the Financial Assessment report was made, where conclusions and recommendations are recorded, which will be used to make decisions, in order to inform the results of the Analysis of the Financial Statements for the years 2014-2015, the application Of a Financial Evaluation of the Lizbeth Supermarket; So that it contains suggestions aimed at improving financial management. 7 When carrying out the financial evaluation of the Lizbeth Supermarket, it is concluded that it maintains a high index of accounts receivable from third parties, evidencing the lack of capacity to cover its short-term obligations, it is the cause to have liquidity, which can cause these Accounts that become bad accounts which does not allow you to recover the cash soon. It is recommended to increase new collection policies related to the periodic application of a Financial Assessment so that the owner manager and the company personnel know the actual situation of the same, to achieve the fulfillment of its objectives and goals, which can achieve a correct Administration based on an efficient economic and financial situation.